2021
DOI: 10.3389/fphar.2021.723218
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Phenytoin and Carbamazepine on GFAP Gene Expression and Mutant GFAP Folding in a Cellular Model of Alexander’s Disease

Abstract: Alexander’s disease (AxD) is a rare, usually relentlessly progressive disorder of astroglial cells in the central nervous system related to mutations in the gene encoding the type III intermediate filament protein, glial fibrillary acidic protein (GFAP). The pathophysiology of AxD is only partially understood. Available data indicate that an excessive GFAP gene expression may play a role. In particular, a “threshold hypothesis” has been reported, suggesting that mutant GFAP representing about 20% of the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, long-term use of these drugs can increase the risk of seizures, especially if there is a history of nerve damage ( 69 ), decreasing the potential widespread use of the drug in patients, especially in type I AxD. Bachetti et al ( 70 ) demonstrated for the first time that carbamazepine and phenytoin could inhibit the expression and folding of pathological GFAP cells, thus leading to the reduced formation of mutant GFAP aggregates. Therefore, carbamazepine and phenytoin sodium may have potential therapeutic effects on AxD, especially in patients with partial epilepsy of AxD.…”
Section: Discussionmentioning
confidence: 99%
“…However, long-term use of these drugs can increase the risk of seizures, especially if there is a history of nerve damage ( 69 ), decreasing the potential widespread use of the drug in patients, especially in type I AxD. Bachetti et al ( 70 ) demonstrated for the first time that carbamazepine and phenytoin could inhibit the expression and folding of pathological GFAP cells, thus leading to the reduced formation of mutant GFAP aggregates. Therefore, carbamazepine and phenytoin sodium may have potential therapeutic effects on AxD, especially in patients with partial epilepsy of AxD.…”
Section: Discussionmentioning
confidence: 99%
“…Alexander disease (AxD) is a relatively rare neurodegenerative disease. It a type of leukodystrophy that typically manifests in infancy, although it can occur later in life [ 38 , 39 ].…”
Section: Alexander Diseasementioning
confidence: 99%
“…Disease can be divided into two types depending on the location of the CNS lesions. Type one is characterized by early-onset convulsions, macrocephaly, progressive psychomotor and cognitive delays, and failure to thrive due to lesions in the forebrain [ 39 ]. Type two manifests as posterior brain lesions and associated symptoms such as palatal myoclonus, ataxia, dysphagia, and morphological dysfunction, and it can occur at any age [ 40 , 41 ].…”
Section: Alexander Diseasementioning
confidence: 99%
See 1 more Smart Citation